Integración e identidad: espacios y sujetos (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
In this article, we explore issues of integration and identity as they relate to the complexity and heterogeneity of contemporary migrations in a globalized world. We suggest a multidimensional conceptual framework, which we relate to the experiences of immigrants in the different environments that they produce and encounter. We connect integration with the most subjective aspects of identity formation, tracingthe sinuous path of identity -national, social, and personal- as it takes shape in adiverse society.
Keywords: Integration; Identity; Migrants